ANALISI KREDIT MACET PADA PT BANK DANAMON INDONESIA TBK UNIT DANAMON SIMPAN PINJAM CABANG LOA JANAN - Rina Masitoh, Suhartina, Elfreda Aplonia Lau (EKONOMIA, 2016)
Analysis of Non Performing Loan in PT Bank Danamon Indonesia Tbk Danamon Simpan Pinjam Branch Unit Loa Janan. Activity of giving loan in PT Bank DanamonIndonesia Tbk Branch Unit Danamon Simpan Pinjam Loa Janan has a purpose for helping develop th business of debtors who are mostly seller or businessman by process of credits which appropriate to the company policy ang the most fundamental is to be appropriate with regulation of Bank Indonesia (central bank) to avoid the non performing loan because the base of a dispensable loan from private bank is the asseeement of advisability from Bank Indonesia.The main issue in this research â€Has the distribution of loan in PT Bank Danamon Indonesia Tbk Unit Damnamon Simpan Pinjam Loa Janan Branch properly done and followed the policy ofÂ Bank Indonesia No. 15/2/PBI/2013 ?â€. The hypothesis in the research is â€The distribution of loan in PT Bank Danamon Indonesia Tbk Unit Danamon Simpan Pinjam Loa Janan Branch has properly done and followed the policy of Bank Indonesia.â€ The theory used in research analys is Accountancy Theory by using comparative analys as the tools where we have to calculate the number of non performing loan debtor and the debtor which include in performing loan category in PT Bank Danamon Indonesia Tbk Unit Danamon Simpan Pinjam Loa Janan Branch.